2024
DOI: 10.3390/jcm13072001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vestibular Phenotypes in Patients with Genetic Hearing Loss

Ji Hyuk Han,
Seong Hoon Bae,
Sun Young Joo
et al.

Abstract: Background: The vestibular phenotypes of patients with genetic hearing loss are poorly understood. Methods: we performed genetic testing including exome sequencing and vestibular function tests to investigate vestibular phenotypes and functions in patients with genetic hearing loss. Results: Among 627 patients, 143 (22.8%) had vestibular symptoms. Genetic variations were confirmed in 45 (31.5%) of the 143 patients. Nineteen deafness genes were linked with vestibular symptoms; the most frequent genes in autosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Therefore, patients with variants in genes responsible for HL may exhibit a phenotype of vestibular dysfunction in addition to the HL phenotype. In a recent comprehensive study on the vestibular phenotype in patients with hereditary HL, decreased vestibular function in caloric tests, cVEMP, and oVEMP was observed in 42%, 57.8%, and 85% of patients, respectively 25 , indicating that vestibular dysfunction is common in patients with hereditary HL. However, few studies have specifically investigated vestibular function in patients with hereditary HL.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, patients with variants in genes responsible for HL may exhibit a phenotype of vestibular dysfunction in addition to the HL phenotype. In a recent comprehensive study on the vestibular phenotype in patients with hereditary HL, decreased vestibular function in caloric tests, cVEMP, and oVEMP was observed in 42%, 57.8%, and 85% of patients, respectively 25 , indicating that vestibular dysfunction is common in patients with hereditary HL. However, few studies have specifically investigated vestibular function in patients with hereditary HL.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding vestibular symptoms, 73% (11/15) of patients with SLC26A4 variants complained of vestibular symptoms, whereas less than 10% of patients with GJB2 (1/13) and CDH23 variants (1/11) complained of vestibular symptoms. In a study on the vestibular symptoms of 627 patients with hereditary hearing loss, 22.8% had these symptoms; moreover, the symptoms were common among patients with COCH and SLC26A4 variants 25 . Our previous large cohort study showed that only three of 75 (4%) patients with GJB2 variants and one out of 25 (4%) patients with DFNB12 complained of episodes of vestibular symptoms 7 , 15 .…”
Section: Discussionmentioning
confidence: 99%